Energy Efficiency in Routing Protocols Applied to Wsn [Eficiencia Energética en Protocolos de Enrutamiento Aplicados a Wsn] - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2016)
The Wireless Sensor Network (WSN), have been technological advances that have improved some features to achieve low cost, low power consumption and tiny sizes in wireless sensor nodes. However, one of the issues still restless in Wireless Sensor Networks is the limited battery power of sensor nodes. This paper, share with mechanisms to achieve energy efficiency in a WSN, focusing particularly on routing protocols. Based on the state of the art, is presented a complete taxonomy of routing protocols used in WSN exposing their level of energy efficiency. © 2016 IEEE.